Uncovering the Truth Through Post-mortem: A Normative Analysis of Murder Victim Autopsies - Juswanto Ade Setiawan; Hasbuddin Khalid; Muhammad Azham Ilham (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to analyze the legal procedures for conducting post-mortems on murder victims in Indonesia and to determine the implications of post-mortems on human rights, particularly the rights of victims and their families, during the investigation of murder crimes. The research, entitled